PENGGUNAAN E-MODUL PEMBELAJARAN FISIKA BERBANTUAN WEBSITE GOOGLE SITES PADA MATERI USAHA DAN ENERGI TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS X SMA NEGERI 13 MAKASAR - Yuliastuti Ansar; H. Hasbullah Azhar; Andi Ferawati Jafar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low physics learning outcomes of Grade X students at SMA Negeri 13 Makassar due to conventional, teacher-centered instruction that primarily emphasized cognitive aspects while neglecting students’ attitudes and skills. Data indicated that only 30% of students achieved the Minimum Mastery Criteria (KKM) of 65. Interviews and learning evaluations also revealed low achievement across learning domains, with 18.51% in knowledge, 22.22% in attitudes, and 11.11% in skills, highlighting the need for more innovative instructional media. This study aimed to determine students’ learning outcomes before and after the implementation of a physics E-Module assisted by the Google Sites website on the topic of work and energy, as well as to examine the differences between the two results. The research employed a quantitative approach using a quasi-experimental design. Data were collected through pre-test and post-test instruments and classroom observations. The data were analyzed using descriptive statistics, categorization, and inferential statistics, including normality, homogeneity, and t-tests. The results showed that before the implementation of the E-Module, only 1 out of 26 students (3.8%) achieved mastery, while after the implementation, the number increased to 12 students (46%). The t-test results indicated a significant difference between learning outcomes before and after the treatment (t_count = -2.331; t_table = 2.779; df = 25). Therefore, the Google Sites-assisted E-Module was effective in improving students’ physics learning outcomes and is recommended as an alternative instructional material to support the implementation of the Independent Curriculum.